2019
DOI: 10.1016/j.ssmph.2019.100385
|View full text |Cite|
|
Sign up to set email alerts
|

Relationships between psychological distress and health behaviors among Canadian adults: Differences based on gender, income, education, immigrant status, and ethnicity

Abstract: Objective Psychosocial health predicts physical health outcomes in both clinical samples and the general population. One mechanism is through relationships with health behaviors. Results might differ based on sociodemographic characteristics such as education, income, ethnicity, and immigrant status. Our objective was to analyze sociodemographic differences in relationships between psychosocial health measures and health behaviors in the general population of Canadian adults. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…Self-reported participation in leisure-time sedentary behaviors in the CCHS was also consistent with other studies, averaging 3.3 h per day. This is similar to our estimates of screen sedentary behavior among men and women in the general population, which ranged from around 18 to 25 h per week (2.6-3.6 h/day) and varied by gender and sociodemographic characteristics [16]. Among pregnant women, studies in the US that assessed responses to 2 questions on time spent watching TV and sitting quietly performing other activities showed an average of 2.6 h of sedentary behavior per day [26].…”
Section: Sedentary Behaviorsupporting
confidence: 88%
See 3 more Smart Citations
“…Self-reported participation in leisure-time sedentary behaviors in the CCHS was also consistent with other studies, averaging 3.3 h per day. This is similar to our estimates of screen sedentary behavior among men and women in the general population, which ranged from around 18 to 25 h per week (2.6-3.6 h/day) and varied by gender and sociodemographic characteristics [16]. Among pregnant women, studies in the US that assessed responses to 2 questions on time spent watching TV and sitting quietly performing other activities showed an average of 2.6 h of sedentary behavior per day [26].…”
Section: Sedentary Behaviorsupporting
confidence: 88%
“…In the general population, greater symptoms of psychological distress, depression, and anxiety predict lower physical activity levels [14,15]. Similarly, our studies among the Canadian general population show that greater psychological distress predicted lower self-reported leisure-time physical activity and greater screen sedentary behavior [16]. Among pregnant women, past studies show that greater pregnancy-specific stress and perceived stress are associated with less exercise [17].…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…The relationship between psychological distress and negative health behaviors is well-supported. For example, one study found an association between general emotional distress and poorer exercise behaviors, i.e., greater sedentariness and reduced physical activity ( St.-Pierre et al, 2019 ). Psychological distress has also been found to predict greater consumption of palatable, non-nutritious foods (e.g., Groesz et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%